Left atrial volume changes are an early marker of end-organ damage in essential hypertension: A multidisciplinary approach to an old problem - ÖZBEN SADIÇ, BESTE; TİGEN, MUSTAFA KÜRŞAT (WILEY, 2017)
PurposeLeft atrial (LA) volume has been shown to be a predictor of adverse cardiovascular outcomes. The aim of this study was to evaluate the relation between LA phasic volumes and hypertensive end-organ damage (EOD), by using real time three-dimensional echocardiography (RT3DE) in patients with essential hypertension (HT). MethodsThe study included 95 essential hypertensive patients (6010years, 37 males). The patients were divided into three according to the presence of EOD, namely microalbuminuria and retinal vascular changes detected by direct ophthalmoscopy. The first group had no EOD. The second group (EOD+ group) had either microalbuminuria or retinal vascular changes while the third group (EOD++ group) had both renal and retinal damage. ResultsThe three groups did not differ with regard to age, sex, or metabolic profile. In RT3DE measurements, there were significant differences in LA phasic volumes (LA maximal volume index, LA minimal volume index, LA pre-atrial contraction volume index, LA total stroke volume index, and LA active stroke volume index, P<.001) among the groups. Moreover, patients with more extended EOD had significantly worse LA reservoir and conduit functions. In the logistic regression analysis, the LA active stroke volume index was an independent predictor of EOD (82% sensitivity and 92% specificity, area under the curve=0.96, P<.001). ConclusionRT3DE measured LA phasic volumes and mechanical functions are associated with hypertensive EOD, which might serve as a surrogate endpoint for determining cardiovascular mortality and morbidity rates in patients with essential HT.
Keywords: hypertension; left atrial volume; three-dimensional echocardiography; CARDIOVASCULAR-DISEASE; ARTERIAL-HYPERTENSION; EUROPEAN ASSOCIATION; PRACTICE GUIDELINES; AMERICAN SOCIETY; ECHOCARDIOGRAPHY; PREVALENCE; MANAGEMENT; RECOMMENDATIONS; EPIDEMIOLOGY